Interactive augmented reality environments for engineering with open systems - Sidhu M.S.; Kang L.C. (2023)
Authoring tools are becoming more powerful nowadays due to technological advancements. In a virtual augmented Reality (AR) environment, authoring tools can be used to imitate reality to a certain point. However by employing open systems as an alternative platform for authoring learning contents, developers need to be aware of the options available to them in the development process. This paper reviews some commonly used open source software that could be employed in developing interactive environments for learning and discusses the potential benefits of these authoring tools for simulating engineering problems. 2011 IEEE.